The Influence of Service Quality, Work Efficiency, and Innovation on Loyalty through Satisfaction - Setiawan, M Bagus Prima; Azis, Anton Mulyono; Siregar, Khairani Ratnasari; Abdullah, Karmilah (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
The shipyard industry in Batam plays a vital role in supporting Indonesia's maritime economy. PT Biro Klasifikasi Indonesia (BKI) Batam Branch, as a national classification body, faces challenges in new ship supervision, including inefficient work areas and limited surveyor resources. This study aims to analyze the influence of service quality, work area efficiency, and service innovation on service loyalty through shipyard satisfaction. A quantitative method using PLS-SEM was employed, involving 129 shipyard respondents. Results show that all three independent variables significantly and positively affect satisfaction, which in turn mediates their influence on service loyalty. The results of the study indicate that service quality, work area efficiency, and service innovation significantly contribute positively to shipyard satisfaction levels, which in turn substantially influence loyalty to the service. Customer satisfaction has been proven to play a significant mediating role in bridging the influence of these three variables on loyalty. These findings support the validity of the Disconfirmation of Expectations theory and underscore the urgency of digital innovation as a strategic approach to enhancing competitive advantage. Therefore, this study recommends improving operational efficiency, conducting continuous technical training, and accelerating digital transformation as priority policies to strengthen the service performance of PT BKI Batam Branch.